Self-assembly and applications of anisotropic nanomaterials: A review. Issue 1 (February 2015) - Thorkelsson, Kari; Bai, Peter; Xu, Ting
Graphical abstract: Highlights: Developed strategies and recent advances in the self-assembly of anisotropic nanomaterials are extensively reviewed. Potential applications of assembled anisotropic nanomaterials in chemical and biological sensing, and energy harvesting and transport are thoroughly explored. Based on recent research developments, we provide perspectives and future research opportunities in anisotropic nanomaterial assembly. Summary: Anisotropic nanoparticles are ideal building blocks for a variety of functional materials due to their unique and anisotropic optical, electronic, magnetic and mechanical properties. Precise control over the orientation and spatial arrangement of these nanomaterials is often requisite to achieve coupling between nanoparticles and thereby translate the properties of individual nanoparticles to macroscopic material properties. The physics and thermodynamics involved in the self-assembly are inherently more complex than isotropic nanoparticles due to the anisotropy within the system. However, the anisotropy also introduces anisotropic nanoparticle surface chemistry and stronger interparticle interactions which could be leveraged to achieve self-assembly. To address these challenges and opportunities, a plethora of strategies have been conceived and developed to induce the self-assembly of anisotropic nanoparticles into desired nanostructures over macroscopic areas and volumes. These strategies involve manipulation of interparticle physical interactions, modification of nanoparticle surface chemistry, application of external fields, and utilization of physically or chemically patterned templates to achieve the required level of spatial and orientational control over the assembly of anisotropic nanoparticles. The resulting ordered anisotropic nanoparticle assemblies display strong plasmonic, electronic, and excitonic coupling, which render these assemblies as ideal materials for chemical and biological sensing, energy harvesting, and many other technological applications. Considering the rapid advancement in this field of research, this review aims to provide an overview of the assembly, applications, and opportunities of anisotropic nanomaterials.